1996
DOI: 10.1002/(sici)1097-4628(19960418)60:3<389::aid-app12>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Surface and interfacial FTIR spectroscopic studies of latexes. XIII. Surfactant exudation in silicone-modified latex films

Abstract: Exudation of sodium dioctylsulfosuccinate (SDOSS) surfactant molecules to the film–substrate (F–S) and film–air (F–A) interfaces in styrene/n‐butyl acrylate (Sty/n‐BA) latex films in the presence of trimethoxysilyl propylmethacrylate (MSMA) molecules was examined by polarized attenuated total reflection Fourier transform infrared (ATR FTIR) spectroscopy. It appears that SDOSS molecules are present at the F–A interface but are not detected at the F–S interface due to their displacement by MSMA. When the second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

1996
1996
2000
2000

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 0 publications
0
16
0
Order By: Relevance
“…Similarly, the 1056 and 1046 cm -1 bands are attributed to the S-O symmetric stretching modes resulting from SO 3 -Na + ‚‚‚COOH and SO 3 -Na + ‚‚‚H 2 O interactions. [1][2][3][4][5][6][7][8][9][10][11][12][13] Trace B of Figure 1 illustrates an ATR spectrum recorded from the F-S interface, and it appears that the bands due to pure SDOSS and/or SDOSS associations are not detected. Thus, comparison of the spectra recorded from both interfaces indicate that, for Sty/n-BA copolymer latex, SDOSS exudes to the F-A interface.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, the 1056 and 1046 cm -1 bands are attributed to the S-O symmetric stretching modes resulting from SO 3 -Na + ‚‚‚COOH and SO 3 -Na + ‚‚‚H 2 O interactions. [1][2][3][4][5][6][7][8][9][10][11][12][13] Trace B of Figure 1 illustrates an ATR spectrum recorded from the F-S interface, and it appears that the bands due to pure SDOSS and/or SDOSS associations are not detected. Thus, comparison of the spectra recorded from both interfaces indicate that, for Sty/n-BA copolymer latex, SDOSS exudes to the F-A interface.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1, traces C and D, shows ATR FT-IR spectra recorded from the F-A and F-S interfaces of p-Sty/p-nBA latex blend, respectively. As seen, only traces of the SDOSS bands at 1056 and 1046 cm -1 due to S-O symmetric stretching modes of SO 3 -Na + ‚‚‚COOH and SO 3 -Na + ‚‚‚H 2 O associations [2][3][4][5][6][7][8][9][10][11] are detected at the F-A interface (trace C), but as compared to the F-S interface (trace D), they are stronger, indicating that only small quantities of SDOSS exude to the F-A interface. Overall, SDOSS bands at 1288, 1259, 1232, 1208, 1181, 1056, and 1046 cm -1 are significantly stronger in trace A than those in trace C, indicating that there is a greater degree of SDOSS accumulation near the F-A interface for copolymer latex than for its counterpart latex blend.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on latex films indicated that the mobility of SDOSS molecules was affected by the compatibility of SDOSS with a polymer matrix, [5][6][7][8][9][10][11][12] temperature (T c ), 13 and glass transition temperature (T g ). 14 However, such factors as latex particle surface hydrophilicity, that not only influence distribution of individual components, but may also significantly affect film formation and the formation of ordered surfactant structures, are important.…”
Section: Introductionmentioning
confidence: 99%
“…As we have already established and cross-referenced with the literature data,g a comparison of the reactivity ratios for styrene and n -BA favors styrene homopolymerization, and the formation of the polystyrene core and poly( n-BA) shell occurs for the larger particle sizes. 13 In contrast, for smaller particle sizes, more homogeneous distribution for S t y / n -BA particle cross-section is anticipated. As a result, the 1056 cm-' band is detected for larger particle-size latexes, but it is not detectable for smaller particles since there are minimal or no COOH ---SO; Na' interactions.…”
Section: Resultsmentioning
confidence: 98%